Halal Tourism in Malaysia: A marketing analysis - Man, Rosilah (Jurnal Penyelidikan Sains Sosial, 2025)
The tourism sector in Malaysia is the country's largest income contributor tourism.gov.my. The halal tourism sector is one of the popular trends nowadays and Malaysia is one of the preferred Muslim travel destinations for Muslim travellers around the world. Nowdays, many Muslim travellers nowadays have the ability either financially or physically to travel. Therefore, this study is conducted to analyze to which extent the marketing strategies made by tour operators were able to attract Muslim travellers to subscribe the package. The survey was distributed via online and a total of 52 samples were obtained. Descriptive analysis was used using SPSS. The result found that Muslim-friendly travellers need a number of criterias that should be reviewed in a tour package especially in terms of halal awareness and information, sensitivity, respect for culture as well as safety and comfort. Some of the items proposed to the agency's travel are such as providing halal-certified food and accommodation that complies with halal standards.The importance of this study is to provide information especially to travel agencies, travel company operators, policy makers and related parties to ensure that the marketing strategies displayed in the advertisements are in line with the needs of Muslim travellers .